Extraction and Characterization of Mango Seed Oil from Mun Duean Kao Cultivar for Cosmetic Applications - Benchawan, Thewika; Kongchantree, Phakawan; Mahadlek, Jongporn (KKU Science Journal, 2025)
This research investigates the extraction and characterization of mango seed oil from the Mun Duean Kao (also known as Tawai Duean Kao) cultivar to enhance its value and utilize this oil in cosmetic products. The physicochemical properties and bioactive compounds of mango seed oil were analyzed and used as an active ingredient in a moisturizer bar product. Mango seed oil and the moisturizer bar were evaluated for antioxidant activity by the DPPH method and tyrosinase inhibitory activity. Reflux extraction using hexane as a solvent at a ratio of 1:3 at 55ºC yielded the highest amount of extracted mango seed oil (8.71%). The oil exhibited good quality and not rancid, with an iodine value of 40.17 ± 0.14 g I2/100 g oil, a saponification value of 200.46 ± 1.03 mg KOH/g oil, an acid value of 2.81 ± 0.06 mg KOH/g oil, a peroxide value of 2.98 ± 0.03 meq peroxide/kg oil, and a viscosity comparable to other vegetable oils (50.51 ± 0.01 cP). The oil contains bioactive compounds, including β-carotene at 3.48 mg/100 g, total phenolic contents at 4.57 mg GAE/g, and vitamin E at 1.51 mg/100 g. Both the oil and the moisturiser bar demonstrated strong antioxidant activity, with IC50 of 0.23 and 0.19 mg/mL, respectively, compared with ascorbic acid (0.18 mg/mL). However, the anti-tyrosinase activity of both remained relatively low, with IC50 of 0.54 and 0.47 mg/mL, respectively, compared with kojic acid (0.02 mg/mL) and ascorbic acid (0.09 mg/mL). The results indicated that mango seed oil can be used in cosmetic products, especially as a natural antioxidant.